Investigation the Effect of ZnO Catalysts Loading and Reaction Time on Polluted River Water Treatment Performance by Using Membrane Photocatalytic Reactor Pilot Plant - MOHAMMAD DZULKIFLI, FARZANA BALQIS (Progress in Engineering Application and Technology, 2023)
The river is the source of human life and the backbone of almost all human activities. As a result, contamination of river water, which contains massive, harmful substances, may have an impact on the sustainability of water resources, population, and economy. A recent advance technology for river treatment is the membrane photocatalytic reactor (MPR), equipped with Zinc oxide (ZnO) as a photocatalyst. Previous study had proven the capability of this MPR and the desired for industrial scale is high. The major obstacle is to provide a pilot scale characteristic before execution at industrial scale. This research explores the correlation of ZnO loading and reaction time on MPR performance. For that purpose, a MPR pilot scale test bench, ZnO loading 0.05 – 0.15 g/L, and reaction time up to 50 minutes at 10 minutes interval is further analyze. The operating condition affirmed and proved that the correlation between ZnO loading, and reaction time managed to treat turbidity, COD, and color up to 90% efficiency. From this research, the optimum removal of contaminants activities within photocatalytic reactor, lays on ZnO loading of 0.15 g/L and 40 minutes, meanwhile for the membrane separation lays on ZnO loading of 0.10 g/L and 10 minutes. The ZnO loading 0.10 g/L yield stable kinetic model and highest membrane flux. The outcome of this research has the potential to be scaled up for polluted river water treatment supply chain systems of the future sector especially in any affected region.